A proposed institutional christian faith formation program of Assumption College-San Lorenzo in the Light of the Way of Faith of St. Marie Eugenie of Jesus - Niverio, Roberto Beria (Animo Repository, 2022)
This study determined the perceptions of the students, faculty and staff on the faith formation activities provided by Assumption College with the Second Plenary Council of the Philippines’ elements of faith and the way of faith of St. Marie Eugenie of Jesus as framework. It accounted how the elements of faith according to PCP II vis-a-vis St Marie Eugenie of Jesus’ way of faith were evident in the respondents’ experiences. This study employed a descriptive quantitative survey research to determine the perceptions on the faith formation activities offered by the school. The participants were students, teachers and staff of Assumption College, Makati Philippines. The primary instruments used in this study were a set of questionnaires. To enhance or verify the survey results, focus group discussion was also conducted using a guide developed by the researcher and validated by three experts in the field of theology, religious education and research. The data collected were interpreted using frequency count, percentage distribution, mean and content analysis. Verbatim remarks generated from focus group discussion were synthesized and used as validation or negation of the survey results therewith. It was concluded that, generally, the current faith formation activities of the school contributed to the spiritual growth of the students, faculty and staff as exhibited by their ratings on the survey. On the other hand, the respondents’ rating also indicated their perceptions on each of the elements of faith through the survey results. Those elements of faith which generated low mean scores suggest the need to propose improvements and additional activities to fill in the gap in the faith formation program based on the perceptions of the respondents. Focus group discussions’ results also revealed some explicit suggestions of the respondents in connection to the improvement of the faith formation program of the school. Both the survey and focus group discussions’ results unveiled the need for more opportunities to be provided by the faith formation program to ensure that a faith grounded in Filipino culture of the teachers, faculty and staff will be given more priority and opportunity in the school. The three groups of respondents indicated the existing faith formation program of the college is still weak in terms of helping them develop a faith that strongly links to their culture as Filipinos. Thus, the outcomes of this study were utilized to constitute as resources and basis in the development of the proposed institutionalized Christian faith formation program of the college in the light of the way of faith of the Assumption’s Mother Foundress, St. Marie Eugenie of Jesus.